Industrial waste management - Mendoza, Rose Marie O. (Delve Publishing, 2019)
Industrial Waste Management studies various aspects of waste management including an extensive overview of industrial waste management and related issues. It includes definitions of waste management, industrial wastes etc. Provides the reader with insights of industrial waste management so as to develop strategies which can further help in efficient management of industrial waste.